An experimental study of flow and heat transfer in a differentially side heated cavity filled with coarse porous media. (November 2019) - Ataei-Dadavi, Iman; Rounaghi, Nima; Chakkingal, Manu; Kenjeres, Sasa; Kleijn, Chris R.; Tummers, Mark J.
Highlights: Heat transfer in a side-heated cavity filled with solid spheres is lower compared to that in a pure-fluid cavity, unless the spheres are highly conductive. The layers of spheres adjacent to the isothermal walls play a prominent role in the heat transfer reduction. The boundary layers along the isothermal walls are partially being diverted towards the inner pores, thus lowering heat transfer. Abstract: Flow and heat transfer in a differentially side heated cubic cavity filled with relatively large solid spheres forming a coarse porous medium have been studied experimentally. Nusselt numbers were measured for Rayleigh numbers between 1.9 × 10 7 and 1.7 × 10 9, solid-to-fluid conductivity ratios between 0.32 and 618, and for different sphere sizes ( d / H = 0.065, 0.14, 0.20), and packing geometries. The heat transfer results indicate that the presence of a porous medium in the cavity decreases the heat transfer compared to the pure-fluid cavity unless the solid spheres are highly conductive. We present a new Nusselt number correlation for coarse porous media based on porous medium dimensionless numbers. Particle image velocimetry and liquid crystal thermography measurements were performed in a refractive index-matched porous medium to obtain pore-scale velocity and temperature fields. The results show that the layers of spheres adjacent to the hot/cold walls play the most prominent role in the heat transfer reduction by hindering the formation of high-velocity boundary layers along the hot/cold walls, causing a portion of the boundary layer fluid to divert away from these walls, thus changing the stratified temperature distribution to a tilted one which leads to a lower overall heat transfer.